Enterprise as an Object of Civil Rights: Basics of the Concept Definition - Yu. V. Baygusheva (Теоретическая и прикладная юриспруденция)
The article highlights points that are essential for defining the concept of an enterprise as an object of civil rights: features of the composition of the enterprise, the factor of combining its elements, as well as the main specifics of concluding and executing transactions regarding the enterprise. Using comparative legal analysis, the author criticizes the interpretation of an enterprise as an immovable property contained in the Civil Code.